Herlyn–Werner–Wunderlich Syndrome: Case report of a newborn presenting with interlabial cyst - Yee Ling Cheong; Narasimhan Kannan Laksmi (Proceedings of Singapore Healthcare, 2019)
A newborn with Herlyn–Werner–Wunderlich Syndrome presented with interlabial cyst. The cyst was punctured and instilled with contrast medium for cystography to demonstrate the anatomy. Simple resection of the hemivagina septum at the same sitting resolved the obstruction. Early interventions done to clinch diagnosis and institute treatment would help to prevent future complications associated with menses retention and preserve fertility.